Clinical and therapeutic outcomes of COVID-19 intensive care units (ICU) patients: a retrospective study in Ghana - Afriyie-Mensah, Jane; Aboagye, Elvis Twumasi; Ganu, Vincent Jessey (My University, 2021)
The COVID-19 pandemic had caused significant morbidity and mortality, with over a million deaths recorded to date. Mortality recorded among severe critically ill patients admitted to intensive care units (ICU) has been significantly high, especially in most COVID-19 epicenters. Reports on the unique clinical characteristics and outcomes from the ICU admissions are on-going with isolated studies in Africa. This study was a retrospective single-centre study involving all polymerase chain reaction (PCR) confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients admitted to the medical intensive care unit (MICU) of the department of medicine and therapeutics, Korle-Bu Teaching Hospital, over the period of 13th April - 28th June 2020. Twenty-two (22) patients in total fulfilled the inclusion criteria and are included in this report. Patients' socio-demographic characteristics, clinical and laboratory parameters outcomes as well as treatment modalities employed were extracted from their respective medical records and analyzed using STATA version 14. Dyspnoea, fever and cough were most common associated symptoms. The mean duration of admission at the ICU was 4.1 ± 3.0 days with five deaths (22.7%). About 91% (20/22) had at least one comorbidity with hypertension as the most prevalent. The median oxygen saturation/fraction of inspired oxygen (SpO2 /FiO2 ) level was significantly higher in persons with only COVID-19 pneumonia compared to those with complicated respiratory failure (p<0.001). Six (27.3%) out of the 22 patients had non-invasive ventilation, with only 1/22 (4.5%) receiving mechanical ventilation. Although non significant, the mean duration of ICU stay was relatively shorter in patients who received therapeutic doses of anticoagulation (p=0.32). Duration of treatment with methylprednisolone was significantly associated with patient outcomes (p=0.04) and serum ferritin levels had a tendency to negatively affect outcome (p=0.06). Clearly there are still no specific targeted medications for COVID19 treatment, except for empirically symptoms guided treatments and management of mild to critically ill patients. Early use of systemic corticosteroids for severe to critically ill patients in the ICU using S/F ratio and CRP levels may improve
Keywords: COVID-19; WACCBIP; Ghana; Intensive care unit; SARS-CoV-2; Samuel Bondzi; Dennis Tetteh; Ernest Kwarteng; Joseph Akamah; Alfred Doku; Patrick Adjei